GABAergic interneurons form transient layer-specific circuits in early postnatal neocortex - Butt, S; Miesenboeck, G; Kätzel, D; Lyngholm, D; Marques-Smith, A; Anastasiades, P; Lickiss, T; Raffiq, S (Nature Publishing Group: Nature Communications, 2016)
GABAergic interneurons play key roles in cortical circuits, yet little is known about their early connectivity. Here we use glutamate uncaging and a novel optogenetic strategy to track changes in the afferent and efferent synaptic connections of developing neocortical interneuron subtypes. We find that Nkx2-1-derived interneurons possess functional synaptic connections prior to emerging pyramidal cell networks. Subsequent interneuron circuit maturation is both subtype and layer dependent. Glutamatergic input onto fast spiking (FS), but not somatostatin-positive, non-FS interneurons increases over development. Interneurons of both subtype located in layers (L)4 and L5b engage in transient circuits that disappear after the somatosensory critical period. These include a pathway mediated by L5b somatostatin-positive interneurons that specifically targets L4 during the first postnatal week. The innervation patterns of immature cortical interneuron circuits are thus neither static nor progressively strengthened but follow a layer-specific choreography of transient connections that differ from those of the adult brain.